From genes to radioresistance in head and neck squamous cell carcinoma - Rodrigues, Joana de Matos (2018)
Head and Neck Cancers (HNC) are a group of tumours located in the upper aero-digestive tract. Head and Neck Squamous Cell Carcinoma (HNSCC) represent about 90% of all HNC cases. It has been considered the sixth most malignant tumour worldwide and, despite clinical and technological advances, the five-year survival rate has not improved much in the last years. Nowadays, HNSCC is well established as a heterogeneous disease and that its development is due to accumulation of genetic events. Apart from the majority of the patients being diagnosed in an advanced stage, HNSCC is also a disease with poor therapeutic outcome. One of the therapeutic approaches is radiotherapy. However, this approach has different drawbacks like the radioresistance acquired by some tumour cells, leading to a worse prognosis. A major knowledge in radiation biology is imperative to improve this type of treatment and avoid late toxicities, maintaining patient quality of life in the subsequent years after treatment. Then, identification of genetic markers associated to radiotherapy response in patients and possible alterations in cells after radiotherapy are essential steps towards an improved diagnosis, higher survival rate and a better life quality. Not much is known about the radiation effects on cells, so, the principal aim of this study was to contribute to a more extensive knowledge about radiation treatment in HNSCC. For this, two commercial cell lines, HSC-3 and BICR-10, were used and characterized resorting to karyotyping, aCGH and MS-MLPA. These cell lines were submitted to different doses of irradiation and the resulting genetic and methylation alterations were evaluated. Our results showed a great difference in radiation response between the two cell lines, allowing the conclusion that HSC-3 was much more radiosensitive than BICR-10. Bearing this in mind, analysis of cell death, cell cycle and DNA damages was performed to try to elucidate the motifs behind this difference. The characterization of both cell lines allowed the confirmation that HSC-3 was derived from a metastatic tumour and the hypothesis that BICR-10 was derived from a dysplasia. Furthermore, this pilot study enabled the suggestion of some genetic and epigenetic alterations that cells suffer after radiation treatment. Additionally, it also allowed the association of some genetic characteristics that could be related to the differences in radiation response observable in this two cell lines. Taken together all of our results contribute to a better understanding of radiation effects on HNSCC allowing one further step towards the prediction of patients’ outcome, better choice of treatment approaches and ultimately a better quality of life.